2011
DOI: 10.1002/sca.20273
|View full text |Cite
|
Sign up to set email alerts
|

Atomic force microscopy of microwear traces on Mousterian tools from Myshtylagty Lagat (Weasel Cave), Russia

Abstract: Since durable technology emerged between 3.4 and 3.2 million years ago, stone tools served as a major material means that hominins used to survive. Determining how different lithic tools functioned is a principal question in human evolution. The main experimentally based approach to the functional study of lithic technology uses stereo and incident-light microscopy, and is known as the Keeley Method. Although this method has demonstrated success in linking the morphology of microwear traces on flint tools to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…; Faulks et al . ; Stemp et al . ) and there have been numerous additional developments involving a variety of new approaches and equipment that have greatly expanded upon earlier work (e.g., Lerner et al .…”
Section: Quantification Of Surface Roughness On Stone Toolsmentioning
confidence: 99%
See 2 more Smart Citations
“…; Faulks et al . ; Stemp et al . ) and there have been numerous additional developments involving a variety of new approaches and equipment that have greatly expanded upon earlier work (e.g., Lerner et al .…”
Section: Quantification Of Surface Roughness On Stone Toolsmentioning
confidence: 99%
“…In the decade or so that followed, more microwear analysts applied techniques and technologies from metrology and tribology to mathematically document the surfaces of stone tools on micro-and nanoscales. In particular, the work of the early practitioners of lithic microwear quantification has continued (e.g., Anderson et al 2006;Faulks et al 2011;Stemp et al 2009) and there have been numerous additional developments involving a variety of new approaches and equipment that have greatly expanded upon earlier work (e.g., Lerner et al 2007Lerner et al , 2010Evans and Donahue 2008;Stevens et al 2010;Evans and Macdonald 2011;Stemp and Chung 2011;Stemp et al 2013Stemp et al , 2015bEvans et al 2014;Lerner 2014;Macdonald 2014;Stemp 2014).…”
Section: Quantification Of Surface Roughness On Stone Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown its potential to infer parameters of the actions performed with a prehistoric artefact, like use duration, worked material, motion direction, or force during use. Many have recently presented protocols attempting to show quantitatively the effect of use duration (Evans et al, 2014;Lerner et al, 2007), worked material (Evans and Donahue, 2008;Faulks et al, 2011;Stemp et al, 2010Stemp et al, , 2009Stemp and Chung, 2011;Stevens et al, 2010) and also direction of motion (Anderson et al, 2006;Vargiolu et al, 2003) on the micro-wear pattern.…”
Section: Introductionmentioning
confidence: 99%
“…Although some lithic use‐wear research has focused on various techniques that rely on two‐dimensional image analysis of worn stone tool surfaces, such as work by Barceló and Pijoan‐López (), Pijoan et al (), Barceló et al (), Dumont (), Gonzalez‐Urquijo and Ibañez‐Estevez (), Grace et al (), and Vila and Gallart (), among others, there has been recent interest in the application of methods that rely on documentation of surface roughness or texture using metrology, specifically laser profilometry (Stemp et al , , , ; see Stemp and Stemp, , ), atomic force microscopy (AFM) (Kimball et al , , ; Faulks et al , ), laser scanning confocal microscopy (LSCM) (Evans and Donahue, ; Evans and MacDonald, ; Stemp and Chung, ; Stevens et al , ), optical interferometry (Anderson et al , , ), and differential contrast microscopy (e.g., Alicona Infinite Focus) (Evans and MacDonald, ). Advantages associated with metrological study of stone surfaces include the production of data in three‐dimensions and the micro‐ to nanoscale level of surface measurement possible.…”
Section: Introductionmentioning
confidence: 99%